2019
DOI: 10.1088/2053-1591/ab52d5
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis to study the effect of infusion of Tetracyanoquinodimethane in zinc based metal-organic framework

Abstract: The present study reports the computational analysis of band structures and density of state (DOS) profiles of a Tetracyanoquinodimethane (TCNQ) infused IRMOF-1 (Iso Reticular Metal-Organic Framework-1). IRMOF-1 is a zinc-based MOF and has been reported useful in literature for a variety of applications, including gas storage and sensing owing to its highly porous structure. We have adopted a SIESTA based computational investigation approach to investigate the tuning of the band structure and DOS of IRMOF-1 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was reported that the electrical conductivity of HKUST-1 can be increased by six orders of magnitude to 7 S/m by doping with 7,7,8,8-tetracyanoquinodimethane (TCNQ), a redox-active organic molecule . Since this pioneering work, much effort has been devoted to the investigation of emergent properties of TCNQ-doped HKUST-1 , and some other MOFs including Co-MOF-74. , Regarding the principles governing charge transport in TCNQ-doped HKUST-1, superexchange electron transport was suggested to explain the low activation energy …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the electrical conductivity of HKUST-1 can be increased by six orders of magnitude to 7 S/m by doping with 7,7,8,8-tetracyanoquinodimethane (TCNQ), a redox-active organic molecule . Since this pioneering work, much effort has been devoted to the investigation of emergent properties of TCNQ-doped HKUST-1 , and some other MOFs including Co-MOF-74. , Regarding the principles governing charge transport in TCNQ-doped HKUST-1, superexchange electron transport was suggested to explain the low activation energy …”
Section: Introductionmentioning
confidence: 99%